It is settlement-experimental research soaking up and exhaust paths GTE of power unit of gas-turbine power stations GTPS with engine NK-16ST - Смирнов, А.В.; Левашов, В.А.; Сидоренко, Д.А.; Гадяка, В.Г.; Маркушин, А.Н. (Eastern-European Journal of Enterprise Technologies, 2010)
Results of design and experimental researches of steadiness of velocity diagram and full pressures at turbine inlet for GT suction duct have been given. Results of design and experimental researches of volute vibration condition for different modes of operation of turbine for GT exhaust duct have been given.